Novel, Deep-Branching Heterotrophic Bacterial Populations Recovered from Thermal Spring Metagenomes - Colman, Daniel R.; Jay, Zackary J.; Inskeep, William P.; Jennings, Ryan deM.; Maas, Kendra R.; Rusch, Douglas B.; Takacs-Vesbach, Cristina D. (Frontiers in Microbiology, 2016)
Thermal spring ecosystems are a valuable resource for the discovery of novel hyperthermophilic Bacteria and Archaea, and harbor deeply-branching lineages that provide insight regarding the nature of early microbial life. We characterized bacterial populations in two circumneutral (pH 8) Yellowstone National Park thermal (T 80 oC) spring filamentous ‘streamer’ communities using random metagenomic DNA sequence to investigate the metabolic potential of these novel populations. Four de novo assemblies representing three abundant, deeply-branching bacterial phylotypes were recovered. Analysis of conserved phylogenetic marker genes indicated that two of the phylotypes represent separate groups of an uncharacterized phylum (for which we propose the candidate phylum name ‘Pyropristinus’). The third new phylotype falls within the proposed Calescamantes phylum. Metabolic reconstructions of the 'Pyropristinus' and Calescamantes populations showed that these organisms appear to be chemoorganoheterotrophs, and have the genomic potential for aerobic respiration and oxidative phosphorylation via archaeal-like V-type, and bacterial F-type ATPases, respectively. A survey of similar phylotypes (> 97% nt identity) within 16S rRNA gene datasets suggest that the newly described organisms are restricted to terrestrial thermal springs ranging from 70 - 90 oC and pH values of 7 - 9. The characterization of these lineages is important for understanding the diversity of deeply-branching bacterial phyla, and their functional role in high-temperature circumneutral ‘streamer’ communities.